Large-Scale Sea Turtle Mortality Events in El Salvador Attributed to Paralytic Shellfish Toxin-Producing Algae Blooms - Amaya, Oscar; Quintanilla, Rebeca; Stacy, Brian A.; Dechraoui Bottein, Marie-Yasmine; Flewelling, Leanne; Hardy, Robert; Dueñas, Celina; Ruiz, Gerardo (Frontiers in Marine Science, 2018)
In late October and early November 2013 and 2017, hundreds of sea turtles were found dead along the Pacific coastline of El Salvador. The dead turtles were in good body condition and did not have any injuries or other major anomalies. In order to determine the role of paralytic shellfish toxins (PSTs) in this mass mortality, tissue samples, including blood, flipper, liver, kidney, stomach and intestinal contents, of dead green turtles (Chelonia mydas) and olive ridley turtles (Lepidochelys olivacea) were analyzed for PSTs using a radioactive receptor binding assay, enzyme-linked immunosorbent assay, and high performance liquid chromatography. Highest values of PSTs were detected in enteric contents in the 2013 event (730.41 μg STX eq 100 g-1) and in gastric contents during the 2017 event (1616.5 μg STX eq 100 g-1). During these events, intense chlorophyll‐A and fluorescence line height anomalies suggestive of algal blooms were identified off the coast of El Salvador. In the 2017 event, Pyrodinium bahamense was observed in samples of gastrointestinal contents from affected sea turtles. Seawater from the region where dead sea turtles were found was also analyzed, but saxitoxin-producing species were found in low abundance (5400 cell/ in 2013 and 672 cell/L in 2017). Although threshold levels of toxicity in sea turtle species are not well-characterized, our evidence suggests that these large events were the result of PST-producing algal blooms and that these blooms are a major cause of sea turtle mortality in this region.